(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In our modern life, the demand and supply of advertising is increasing day by day. It is becoming a crucial part of the century in order to increase sales with relevant ideas about the product. It follows that advertising has a significant impact on society. In our social life, it can also show the level of literacy of the nation. It plays an important role not only in marketing and economy, but also in political, spiritual, educational and mainly linguistic spheres. The word “advertising” appeared in different periods and under the influence of different external factors. The word advertising is defined in the explanatory dictionary of the Uzbek language as follows: it is derived from the words “reclamare” (from Latin) and “reclamer” (from French), the root of this word is “announcement” means “to do” or “to report”226 Advertising is central to the creation and maintenance of the wider meaning.